Media Monitoring of Soros Foundation Activities Worldwide
The collection contains 302 analog tapes and digital discs with edited and unedited footage, including amateur footage, raw footage, documentaries, event recordings, interviews, news reports, promotional videos, television programs and radio recordings, concerning George Soros and the activities of his foundations throughout the world. The most significant part of the collection consists of news reports, media monitoring, and television programs – predominantly from the Western media - about George Soros, the initiatives and projects of Open Society Foundations, and the economical, social, and political issues of the 1990s and early 2000s. The collection also features a large number of documentaries on both George Soros and the specific issues that his foundations were engaged with, with a focus on human rights and sustainable development. To a smaller extent it contains interviews and recordings of various events where George Soros took presence, including economic and academic forums. Reports, film excerpts, and radio recordings, as well as educational and promotional videos form the rest of the collection and they center around events and issues related to the activities of the foundations in Eastern Europe and the United States. Accruals not expected